2001
DOI: 10.1155/2001/213953
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Asthma Management Guideline Dissemination on the Control of Asthma in the Community

Abstract: OBJECTIVE: To measure the impact of asthma management education on the control of asthma in the community.DESIGN: A cross-sectional study comparing three communities.SETTING: Three rural communities in southern Alberta.PATIENTS AND METHODS: A population sample of patients with asthma attending a pharmacy to fill a prescription for asthma medication were selected from three communities. Patients were asked to complete a questionnaire relating to their asthma management and control.INTERVENTION: Three levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
(21 reference statements)
0
8
0
4
Order By: Relevance
“…We identified 7 studies 17,18,52,53,56,58,87 involving interactive seminars, structured training, and medical grand rounds. One study reported statistically significant reduction in ED visits (only in a subgroup of low-income participants; -1.23 visits per year, P = .001) and in the overall annual hospitalization rate.…”
Section: Education Onlymentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 7 studies 17,18,52,53,56,58,87 involving interactive seminars, structured training, and medical grand rounds. One study reported statistically significant reduction in ED visits (only in a subgroup of low-income participants; -1.23 visits per year, P = .001) and in the overall annual hospitalization rate.…”
Section: Education Onlymentioning
confidence: 99%
“…18,50,53,56,86 Three RCTs used structured training, seminars, and workshops for health care providers to examine the effects on missed school. They reported small but statistically nonsignificant reductions in missed school (0.6-4 days).…”
Section: Education Onlymentioning
confidence: 99%
See 1 more Smart Citation
“…(117) No Brasil, as pesquisas também demonstraram os benefícios desses programas no controle clínico da doença, nos custos diretos e também na qualidade de vida tanto de adultos como de crianças. (118)(119) A educação em asma pode ser direcionada a diferentes públicos: população em geral -informar que a asma é uma doença pulmonar crônica que, se adequadamente tratada, pode ser controlada, permitindo uma vida normal; profissionais ligados à saúde -garantir o diagnóstico correto e a recomendação terapêutica adequada para, conseqüen-temente, diminuir a morbidade e a mortalidade; (121) asmáticos -devem ser educados a reconhecer os sintomas, conhecer os fatores desencadeantes e como evitá-los, a participar ativamente do tratamento, identificando os medicamentos e conhecendo as ações a serem tomadas conforme a evolução da doença; (122) familiares e cuidadores -no sentido de se sentirem confortados com as condutas a serem adotadas em relação à evolução da doença; educação nas escolas, empresas públicas e privadas, e seguradoras de saúde -como lidar com a morbidade e a mortalidade relacionadas à asma. (123) Quanto à forma os programas podem ser informativos ou estruturados.…”
Section: Anti-il-5unclassified
“…(124)(125) O estruturado confere melhores resultados e possui os seguintes requisitos: informação educacional que utiliza as formas escrita, verbal, visual e/ou auditiva; linguagem acessível e adaptada à população-alvo; monitorização dos sintomas e/ou do PFE (usar escores de sintomas, e/ou de uso de broncodilatador e/ou de PFE); consulta médica regular (reavaliação programada do paciente pelo médico e por outros profissionais de saúde); plano de ação individual por escrito que deve ser explicado e entregue ao paciente. (117)(118)(119)(120)(121)(122)(123)(124)(125)(126) O conteúdo básico de um programa de asma é apresentado no Quadro 12. (115) O plano de ação por escrito pode ser colocado em prática pelo próprio paciente (automanejo) e planejado em parceria de acordo com os itens do Quadro 12 e o modelo apresentado no Quadro 13 (Quadro 14).…”
Section: Anti-il-5unclassified